Preparing a nation for autonomous vehicles: opportunities, barriers and policy recommendations - Fagnant, Daniel J.; Kockelman, Kara (Transportation research. Part A, Policy and practice, 2015)
•Autonomous vehicles may lead to safer roads, less congestion and reduced parking.•AVs may also result in fewer vehicles per capita, but more VMT overall.•Each AV is estimated to provide $2000–$4750 per year in societal benefits.•AV barriers include cost, liability, licensing, security, and privacy concerns. Autonomous vehicles (AVs) represent a potentially disruptive yet beneficial change to our transportation system. This new technology has the potential to impact vehicle safety, congestion, and travel behavior. All told, major social AV impacts in the form of crash savings, travel time reduction, fuel efficiency and parking benefits are estimated to approach $2000 to per year per AV, and may eventually approach nearly $4000 when comprehensive crash costs are accounted for. Yet barriers to implementation and mass-market penetration remain. Initial costs will likely be unaffordable. Licensing and testing standards in the U.S. are being developed at the state level, rather than nationally, which may lead to inconsistencies across states. Liability details remain undefined, security concerns linger, and without new privacy standards, a default lack of privacy for personal travel may become the norm. The impacts and interactions with other components of the transportation system, as well as implementation details, remain uncertain. To address these concerns, the federal government should expand research in these areas and create a nationally recognized licensing framework for AVs, determining appropriate standards for liability, security, and data privacy.